Ibn ‘Arabī and the Spiritual Sīrah of Prophet Muḥammad - Lala, Ismail (Religions, 2023)
While most traditional works on the life of Prophet Muḥammad focus on how his ostensible teachings and actions can be used as a template for human conduct, the thirteenth-century Sufi thinker, Muḥyī al-Dīn ibn ‘Arabī (d. 638/1240), turns his attention to the spiritual significance and inner reality of Prophet Muḥammad. Ibn ‘Arabī argues that as the seal of the prophets, Muḥammad was not only given the Qur’an, which incorporated elements from previous revelations, nor was he just given a religion that had elements from prior religions; rather, in his very spiritual essence, he combined the essences of previous prophets. It is in this sense that Muḥammad represents the culmination of the prophetic life. In his Fuṣūṣ al-ḥikam, Ibn ‘Arabī reveals the spiritual significance of all the prophets mentioned in the Qur’an, with the exception of Khālid ibn Sinān, whom Ibn ‘Arabī considers to be a prophet and dedicates a chapter to, but who is not mentioned in the Qur’an. The present paper explores how the spiritual essences of previous prophets are manifested in Prophet Muḥammad, and the ways in which this comprehensiveness is exhibited in his life. This ‘spiritual sīrah’ is all the more significant in the modern context, where spirituality is privileged over religiosity. Ibn ‘Arabī demonstrates that the spiritual basis of the life of Prophet Muḥammad cannot be extricated from his external actions. The ‘spiritual sīrah’ thus provides an antidote to the religious associational formalism that is rejected by many modern Muslims.